The The Influence of Physical Work Environment, Psychological Work Environment, Work-Life Balance, and Internal Communication on Employee Job Satisfaction during the Hybrid Working Era - Febrian, Wenny Desty; Magito, Magito (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The shift toward hybrid work systems following the pandemic has introduced new challenges in human resource management, particularly concerning employee job satisfaction. This study aims to examine the influence of physical work environment, psychological work environment, work-life balance, and internal communication on employee job satisfaction. A quantitative research approach was used through a survey of 200 employees working in hybrid settings. The research instrument consisted of a Likert-scale questionnaire, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that all four independent variables have a positive and significant influence on job satisfaction, with the psychological work environment having the strongest effect. These findings highlight the importance of creating physically and psychologically supportive work environments, maintaining work-life balance, and fostering effective internal communication to enhance job satisfaction in hybrid work contexts.